The Use of Youtube Media in Improving Students' Narrative Text Writing Ability in High Schools - Khaerul Lisna Diniyanti; Arso Setyaji; Maria Yosepin (Institut Agama Islam Sunan Giri Ponorogo, 2022)
The aims of this study were (1) to determine the students' ability in writing narrative texts through youtube audio videos at SMAN 2 Pemalang, (2) to determine students' abilities in writing narrative texts without youtube audio videos at SMAN 2 Pemalang, (3) to determine the difference in the ability to write narrative text thinking with and without youtube video audio. This type of research is quantitative. The research design used by the author is a quasi-experimental. The population in this study were students of class X SMAN 2 Pemalang totaling 330 students. The number of samples is 72 students which are divided into two classes. For class X2 as the control group and class X1 as the experimental group. The instrument data used in the form of tests consisting of pre-test and post-test. The results showed that (1) the students' ability in writing narrative texts without using youtube videos was adequate, this could be seen from the average test score of 76.33; (2) students' ability to write narrative texts using YouTube videos is good. It can be seen through the average test score is 82.63; (3) there is a significant difference in students' abilities in writing narrative texts without using youtube videos and using youtube videos. This can be seen from the t-test value which is higher than the t-table (3.23 > 1.67). Thus, Ha shows that there is a significant difference in students' abilities in writing narrative texts taught using youtube videos is accepted and Ho which states that there is no significant difference in students' abilities in writing narrative texts taught using youtube videos is rejected. Then it is recommended for English teachers to use youtube media in the teaching and learning process to make it more interesting, so that students will be motivated to practice writingThe aims of this study were (1) to determine the students' ability in writing narrative texts through youtube audio videos at SMAN 2 Pemalang, (2) to determine students' abilities in writing narrative texts without youtube audio videos at SMAN 2 Pemalang, (3) to determine the difference in the ability to write narrative text thinking with and without youtube video audio. This type of research is quantitative. The research design used by the author is a quasi-experimental. The population in this study were students of class X SMAN 2 Pemalang totaling 330 students. The number of samples is 72 students which are divided into two classes. For class X2 as the control group and class X1 as the experimental group. The instrument data used in the form of tests consisting of pre-test and post-test. The results showed that (1) the students' ability in writing narrative texts without using youtube videos was adequate, this could be seen from the average test score of 76.33; (2) students' ability to write narrative texts using YouTube videos is good. It can be seen through the average test score is 82.63; (3) there is a significant difference in students' abilities in writing narrative texts without using youtube videos and using youtube videos. This can be seen from the t-test value which is higher than the t-table (3.23 > 1.67). Thus, Ha shows that there is a significant difference in students' abilities in writing narrative texts taught using youtube videos is accepted and Ho which states that there is no significant difference in students' abilities in writing narrative texts taught using youtube videos is rejected. Then it is recommended for English teachers to use youtube media in the teaching and learning process to make it more interesting, so that students will be motivated to practice writing